Relevant Membrane Transport Proteins as Possible Gatekeepers for Effective Pharmacological Ascorbate Treatment in Cancer - Christian Leischner; Luigi Marongiu; Alban Piotrowsky; Heike Niessner; Sascha Venturelli; Markus Burkard; Olga Renner (MDPI AG, 2023)
Despite the increasing number of newly diagnosed malignancies worldwide, therapeutic options for some tumor diseases are unfortunately still limited. Interestingly, preclinical but also some clinical data suggest that the administration of pharmacological ascorbate seems to respond well, especially in some aggressively growing tumor entities. The membrane transport and channel proteins are highly relevant for the use of pharmacological ascorbate in cancer therapy and are involved in the transfer of active substances such as ascorbate, hydrogen peroxide, and iron that predominantly must enter malignant cells to induce antiproliferative effects and especially ferroptosis. In this review, the relevant conveying proteins from cellular surfaces are presented as an integral part of the efficacy of pharmacological ascorbate, considering the already known genetic and functional features in tumor tissues. Accordingly, candidates for diagnostic markers and therapeutic targets are mentioned.